2017
DOI: 10.1016/j.wem.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

L-arginine Attenuates Hypobaric Hypoxia-Induced Increase in Ornithine Decarboxylase 1

Abstract: L-arginine attenuates acute hypobaric hypoxia-induced increase in mean pulmonary artery pressure and ODC1 gene expression in lung tissues of rats. ODC1 gene contributes to the development of hypoxic pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…bulgaricus. The existing research also confirms that injecting arginine can reduce patients' AMS scores [51] and alleviate mean pulmonary artery pressure in rat lung tissue caused by acute hypobaric hypoxia [52]. It is necessary to precisely detect the levels of arginine and tyrosine in mouse feces through targeted metabolomic approaches next, to explore their relationship with acute hypoxic injury in mice.…”
Section: Discussionmentioning
confidence: 87%
“…bulgaricus. The existing research also confirms that injecting arginine can reduce patients' AMS scores [51] and alleviate mean pulmonary artery pressure in rat lung tissue caused by acute hypobaric hypoxia [52]. It is necessary to precisely detect the levels of arginine and tyrosine in mouse feces through targeted metabolomic approaches next, to explore their relationship with acute hypoxic injury in mice.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, the HT group of greater amberjack was found to produce a significant downregulation of the odc1 gene relative to the HS group when exposed to hypoxic stress, resulting in the inhibition of antioxidant activity. ODC1 (ornithine decarboxylase1), encoded by odc1, is the rate-limiting enzyme for the synthesis of polyamines [45], which play a key role in cell proliferation, differentiation, and antioxidation [46]. Furthermore, the expression of odc1 was significantly correlated with the antioxidant activity of GSH (glutathione).…”
Section: Antioxidant Effect and Apoptosismentioning
confidence: 99%